Pseudothecium development and ascospore discharge in Venturia asperata and V. inaequalis: relation to environmental triggers - Daniele PRODORUTTI; Valeria GUALANDRI; Vincent PHILION; Arne STENSVAND; Emanuela COLLER; Ilaria PERTOT (Phytopathologia Mediterranea)
Venturia asperata (Ascomycetes) was first described in 1975, as a saprotroph on overwintered apple leaf litter, and then, in 2007, as the cause of atypical apple scab symptoms on scab-resistant apple cultivars in southern France, and later in northern Italy and China. Information on V. asperata is limited. This study expanded knowledge by comparing development of pseudothecia and ascospore discharge in V. asperata and V. inaequalis. Leaf litters with pseudothecia of V. asperata or V. inaequalis were prepared, and a spore trap was placed above each litter. Over the 2-year study, pseudothecia of the two pathogens developed differently: V. asperata had delayed pseudothecium maturation and emptying in relation to degree day accumulation, compared to V. inaequalis. The ascospore release for V. asperata was also delayed, commencing and ending later than V. inaequalis. The delayed spore ejection and pseudothecium development of V. asperata compared to V. inaequalis may partly explain the late onset of symptoms in orchards during each growing season. These results have implications for plant protection strategies on scab-resistant apple cultivars, in particular under warm climates that occur in the Mediterranean region.